2010
DOI: 10.1038/ijo.2009.294
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution and obesity: resistance of obese-prone rats to a challenge of food restriction and wheel running

Abstract: The adaptive hypothesis that an obese-prone genotype confers a fitness advantage when challenged with food restriction and food-related locomotion was tested using a rat model. Juvenile (35-40 days) and adolescent (45-50 days) JCR:LA-cp rats, obese prone (cp/cp) and lean prone ( þ /?), were exposed to 1.5 h daily meals and 22.5 h of voluntary wheel running, a procedure that normally leads to self-starvation. Genotype had a dramatic effect on survival of rats when exposed to the challenge of food restriction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…On average, O/PCOS-prone rats raised on free access to food lasted 2.4 times longer than Lean-FF rats under the AAC, replicating our recent findings in obese-prone, male JCR rats (29). Age-matched JCR female rats, prone to obesity and PCOS, survived longer in the AAC than male obese-prone rats, demonstrating an additional survival benefit of the PCOS genotype.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On average, O/PCOS-prone rats raised on free access to food lasted 2.4 times longer than Lean-FF rats under the AAC, replicating our recent findings in obese-prone, male JCR rats (29). Age-matched JCR female rats, prone to obesity and PCOS, survived longer in the AAC than male obese-prone rats, demonstrating an additional survival benefit of the PCOS genotype.…”
Section: Discussionsupporting
confidence: 85%
“…rats. This supports the notion that genotype and food environment contribute to survival during unpredictable periods of food shortage (29). However, less is known about the survival benefit of a PCOS background associated with the obese-prone (cp/cp) genotype in suboptimal nutritional environments.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…60,61 Levels of plasma aldosterone, renin, and norepinephrine follow similar patterns to those observed in humans with CHF. Although multiple studies have demonstrated the beneficial effects of physical activity, CR, and body weight reduction on survival, 62,63 there is a lack of information regarding the effects of fasting in this model. The outcome of such a study would be of great clinical impact considering that coronary heart disease (CHD), hypertension and, in the long term, the use of certain chemotherapy drugs can lead to the development of CHF.…”
Section: Rat Knockout and Transgenic Modelsmentioning
confidence: 99%
“…The concept of reinforcement is thoroughly established in earlier chapters, so this section is wellsuited to support the concept through discussion of ontogenetic adaptability (Glenn 1991), computer analogs (McDowell and Popa 2010), neuroscience (Donahoe 2002), and genetics (Pierce et al 2010). Finally, selection on a cultural level is introduced and discussed.…”
Section: Chapter Highlightsmentioning
confidence: 99%